INFLOW CONTROL DEVICE (ICD) MODELING AND PRODUCTION PREDICTION IN HORIZONTAL WELL FOR X FIELD - RESTUNING AGUSTINA (NIM : 22209048), JATI
X Field is located in west of Natuna Sea and part of Riau Island Province. X Field has sandstone reservoir and produces oil with gas cap and water drive. A horizontal well which is A-22 well was planned for developing and increasing oil production in X Field. Although horizontal well can result in productivity increase in its early life, a problem like uniform pressure drop along horizontal section may occur, which in turn can lead to early breakthrough of water and/or gas. Breakthrough typically occurs in region of high permeability or at the heel of the lateral section in homogeneous reservoir. This ultimately will lead to a reduction in EUR and well performance. Inflow Control Device (ICD) is a completion device which is used to mitigate early water and/or gas breakthrough problems for horizontal well. ICD will uniform the drawdown along the horizontal section. Dynamic modeling is necessary to be conducted in order to analyze the effect of ICD in horizontal well. Thus, well production fluctuation can be monitored for a required time range. To predict reservoir productivity in X Field in the future, saturated reservoir was modeled in 3-D and three phases with reservoir simulation using Black Oil Simulator Eclipse 100 software with the size of 15 grids in X axis, 117 grids in Y axis and 13 grid in Z axis with a total of 22,815 grids. In this reservoir simulation, well segmentation was utilized to model the ICD in horizontal well in order to determine the effect of kinetic pressure loss in ICD and to model the flow of some segments from the formation to borehole and to ICD valve. ICD segment modeling was conducted using a predetermined valve which was fit with ICD valve diameter with keyword WSEGVALVE that computed the valve diameter and valve amount. Packers were used above and below the valve for segmentation purpose. A-22 well data are 3-D geological model data, porosity distribution, permeability, planned well trajectory and planned well completion. Prediction modeling was only done for A-22 well using 7 scenarios with time line of 10 years.